Guns 360: differing perspectives and common-sense approaches to firearms in America - See, Eric S.; Bellas, Christopher M.; See, Sarah A. (Rowman & Littlefield, 2022)
"Guns 360 takes a comprehensive, interdisciplinary, and common-sense approach to some of the most difficult issues facing not only the criminal justice system but also society as a whole: firearm possession, regulation, and control"--